Enhancing biogas generation via anaerobic co-digestion of Cow dung and durian peel waste - Silvalingam Selvalingam (2024)
This study addresses the pressing challenges of municipal solid waste (MSW) management, particularly in Malaysia, where open dumping landfills are prevalent, leading to severe environmental impacts, including contributions to global warming due to the release of greenhouse gases. The study focuses on leveraging durian biomass waste and cow dung for biogas production through anaerobic co-digestion. This choice of feedstock is motivated by the substantial amount of durian peel waste generated annually (350,000 MT) and the significant increase (50%) in methane emissions from cow dung over the past 15 years. By understanding the composition of these feedstocks and their potential for large-scale utilization, the study aims to address the challenges associated with municipal solid waste management. The objective of the experiments was to evaluate the efficiency of biogas production, considering various parameters such as feedstock ratios, durian peel sizes, pH levels, and working volumes, to optimize biogas generation. Two anaerobic digestion experiments were conducted at room temperature. The first experiment involved 40g of mixed waste with a 53.3% working volume undergoing a 2-week anaerobic digestion, while the second experiment utilized 100g of mixed waste with a 91.7% working volume and 0.25mm durian peel particles, spanning 21 days. Methane detection was carried out using methane gas detectors, and microbial identification provided insights into biogas composition and microbial roles. Despite challenges such as pH fluctuations, the study underscores the importance of careful system design for efficient biogas production. Anaerobic co digestion demonstrated superior efficiency over mono digestion, particularly with a 2:1 ratio of cow dung to durian peel, which maximized biogas production. Smaller durian peel particle sizes, specifically 0.25mm and 0.5mm, were found to enhance methane generation, highlighting the significance of pre-treatment processes. Overall, the study contributes valuable insights into optimizing biogas production from durian biomass waste and cow dung, offering promising solutions for sustainable MSW management and mitigation of environmental impacts.